Kelios pastabos apie prūsų kalbos daiktavardžių ī kamieno raidą - Ambrazas, Saulius (Baltistica, 1995)
SOME REMARKS TO THE DEVELOPMENT OF SUBSTANTIVES WITH ī STEM IN OLD PRUSSIANSome Old Prussian substantives with ī stem, especially mary (Hab) E 65, plauty (Lange) E 126, sari (Glut) E 43, which came back from nomina collectiva, are very old. The other part of them is supposed to be the result of contamination of ī, i̯ā and (i̯)ē stems, cf. OPr. asy (Reen) E 241 and Lith. ežià, Latv. eža „boundary”, OPr. pelky (Bruch) E 287 and Lith. pélkė, Latv. pel̃ce „swamp, marsh”. The similar process took place also in West Lithuanian dialects (they can be descended from West Baltic too).
Keywords: prūsų kalba; daiktavardis; i-kamienas